Día de los muertos para meus finados: hibridismo cultural a partir da ressignificação de elementos - Colvero, Aracy Maura Vieira (2019)
The present dissertation approaches a reflection about the re - signification and reinterpretation of elements, generated by the hybridism between the celebrations of Dia de los Muertos, aspect of the Mexican culture and the Day of the Dead, aspect of the culture in which I am inserted. It is a research based on reflexive autoethnography that implied biographical research, memories and coexistence with cultural members, where the actions and field work were documented, as well as the changes that occurred in the research through the results of this field work enabling the elaboration of reinterpreted and re-signified elements, inserted in the poetic construction developed from installation, photography and engraving. The text presents a theoretical discussion about the history of Death in cultures and celebrations today, as well as the justification by the election of the term hybridism for use in this research. I present the creative process and the visual thought expressed in the images that were made. The works developed are composed of two parts, a photograph and a metal engraving, which represent visually the change of perspective, not only of the elaboration of Death, but of the very reworking that we do about the culture of the other.